"A deficiência já limita, não posso limitar minha sexualidade": um estudo sobre corpo e sexualidade a partir da paralisia cerebral - Cunha, Luana Santos (2020)
The present study asks about the senses attributed to the sexuality of people with cerebral palsy prioritizing the perception of the own individuals. This thesis defends the invisibility of the sexuality of people with cerebral palsy who claim, in addition to citizenship, sexual and reproductive rights. For this purpose, it starts from reports about what means to live with cerebral palsy focusing the experiences that revolve around sexuality, not forgetting to perform a discussion related to the body, autonomy and the notion of person based on Disability studies theoretical contribution. The construction of the body as something social, suggests an idea of perfection, completeness, beauty and ability, therefore sought to understand as such conceptions imply in social dynamics, projections and expectations that we build about human subject who affect the individual’s life, located in the world of working, but also in the family, in sociability and in affective relationships, among others spheres of social life. The discussion about these questions was realized based on construction and analysis of narrative about the body and sexuality through daily reports of people with cerebral palsy which brought up questions about stigmas, the family formation process involving discussions about conjugality, parenting and narrative about autonomy. The research concludes existence of a plurality of senses about what we understand by person, taking into account the difference of genre, institutional inclusion, relationships, lifestyles, moment of life’s course, independence and activisms mainly when we comprehend that the sphere of sexuality can’t be unlinked of political discussions, as Gayle Rubin remind us, the importance of a new view for the internal political of the sexuality, disparities and forms of oppression.